Conversational maxims in encounters with law enforcement officers - Linfoot-Ham, Kerry (International Journal of Speech, Language and the Law, 2006)
This paper analyses the use of spoken language by suspects and witnesses being questioned by law enforcement officers. The aim is to discover whether, and to what extent, Grice’s (1975) Cooperative Principle is in evidence, and how adherence to or breaking the conversational maxims helps or hinders the interrogation process. Following conclusions derived from the analysis, possible explanations as to why some suspects are arrested or taken into custody, whereas others are allowed to go free are put forth. The possibility will be considered that successful manipulation of Grice’s Cooperative Principle (and the associated conversational maxims) may have some degree of subconscious influence on police officers’ decisions regarding a suspect’s guilt or innocence